Analisis Pengaruh Penggunaan Social Media Marketing Melalui Instagram Terhadap Keputusan Pembelian, Studi Kasus Pada Program Studi Manajemen S1 Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut - Syafarudin, Dadang (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This study aims to determine and analyze the influence of social media marketing on decision making. Social media as an independent variable has influenced consumer behavior in buying a product, including in the world of education which is an intangible product. Social media marketing for prospective new students currently has a close relationship with the purchasing decision to choose the college they will go to. The method that the writer will use is to use a quantitative method, namely a research method based on a hunch of positivism, used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative/statistical in nature, with the aim of testing the hypotheses that have been set.